2020
DOI: 10.3892/mmr.2020.10953
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bao Gui capsule in treatment of a polycystic ovary syndrome rat model

Abstract: The present study was designed to elucidate the underlying mechanisms of Bao Gui capsule (BGc) against hyperandrogenism, insulin resistance and leptin resistance of PcoS. letrozole was used to induce a PcoS model in rats, which were then randomly divided into four groups (n=9): control, Model, high-dose BGc (BGc-H) and low-dose BGc (BGc-l) group. Serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (lH), testosterone (T), estradiol (e 2 ), insulin, leptin, and interleukin (il)-1β, il-6 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…2 . Catechins, Sahoyao-gancao decoction, Bao Gui capsule, Cangfu Daotan decoction and nanocurcumin inhibited NF-ΚB mediated inflammation by decreasing the expression of phosphorylated NF-kappa-B p65 (p–NF–κB p65), IL-1α, IL-6, and TNF- α [ 16 , 38 , 39 , 51 , 69 ]. Moreover, studies found that Resveratrol, Berberis (B.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 . Catechins, Sahoyao-gancao decoction, Bao Gui capsule, Cangfu Daotan decoction and nanocurcumin inhibited NF-ΚB mediated inflammation by decreasing the expression of phosphorylated NF-kappa-B p65 (p–NF–κB p65), IL-1α, IL-6, and TNF- α [ 16 , 38 , 39 , 51 , 69 ]. Moreover, studies found that Resveratrol, Berberis (B.)…”
Section: Discussionmentioning
confidence: 99%
“…The hydroalcoholic extract of flaxseed was effective in serum hormone levels and polycystic ovarian morphology [ 37 ]. Bao Gui capsule (BGC) attenuated hyperandrogenism via increasing Cyp19a1 and down-regulating P450c17 [ 38 ]. It also ameliorated insulin resistance and detracted some inflammatory markers and IKK /NF- signaling.…”
Section: The Promising Evidence Of Natural Products In Modern Drug Di...mentioning
confidence: 99%
“…SGD might reduce the phosphorylation of nuclear factor kappa-B (NF-kB) p65, suppress toll like receptor 4 (TLR4)/NF-kB signaling pathway, remodel gut microbiome structure, and protect gut barrier, which leads to ameliorate the inflammatory response in the ovary of PCOS rats [ 25 , 33 ]. As the most effective formula to reduce high testosterone, BGC decreased the expression of P450c17 α and increased the expression of P450arom to improve hyperandrogenism [ 30 ]. There were also studies on the effect of CHM on ovarian granule cell apoptosis through the PKR-like Reticulum Kinase (PERK)-ATK4- C/EBP homologous protein (CHOP) signaling pathway, PI3K/AKT/mTOR pathway, and P13K/AKT/Forkhead Box Protein O1A (FOXO1A) pathway [ 15 , 23 , 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 expression was found to increase in a mouse model of PCOS. It mediates chronic low-grade inflammation of the endometrium and produces various metabolic disorders, thereby reducing endometrial receptivity [ 48 ].…”
Section: Characteristics Of Endometrial Receptivity Markers In Pcos Patients During the Implantation Windowmentioning
confidence: 99%